Illegal enrichment: analysis of novelty of criminal law - Кубальський, Владислав Нарцизович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The problems of introduction of a special article for illegal enrichment of the Criminal Code of Ukraineare examined. The conclusion is drawn that this corresponds to the introduction of international law in thisarea and provides law enforcement agencies of Ukraine extra legal means to deal with corrupt enrichment.